Implementasi Kebijakan Pelayanan Administrasi Terpadu Kecamatan Perspektif Peraturan Menteri Dalam Negeri Nomor 4 Tahun 2010 Dan Fiqih Siyasah - Imas Nurjamillah; Siti Ngainnur Rohmah; Munawir Sajali (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
District Integrated Administrative Service which is a service innovation to close the distance between the government as a service provider and the community as a service recipient, which is based on the delegation of authority from the Regent to the Camat as regulated in the Minister of Home Affairs Regulation Number 4 of 2010 concerning Guidelines for Integrated Administrative Services District (PATEN). The purpose of this study is to describe the Implementation of District Integrated Administrative Services in Gantar District, Indramayu Regency Perspective of the Minister of Home Affairs Regulation Number 4 of 2010 and in Fiqih Siyasah. The research method used is a qualitative research method with a descriptive analysis research approach. The results of the research on the Implementation of District Integrated Admission Services (PATEN) from the perspective of Minister of Home Affairs Regulation No. 4 of 2010 Gantar District have fulfilled the requirements for PATEN administration both in terms of substantive, administrative, and technical requirements. The factors that influence the success of policy implementation are good communication, disposition, and bureaucratic structure that can make PATEN implementation run well. The implementation of the PATEN policy in Fiqh siyasah that occurred in the Gantar sub-district was quite good, to realize perfection in carrying out administrative services there were two indicators, namely fast in service, and professional in handling. However, this indicator shows that administrative services at the Gantar District Head Office in the Regency still need to be improved even better.Keywords: Policy; PATEN; Fiqih Siyasah Abstrak: Pelayanan Administrasi Terpadu Kecamatan yang merupakan suatu inovasi pelayanan guna mendekatkan jarak antara pemerintah sebagai penyedia layanan dengan masyarakat sebagai penerima layanan, yang sejatinya didasari oleh adanya pendelegasian kewenangan dari Bupati kepada Camat yang diatur pada Peraturan Menteri Dalam Negeri Nomor 4 Tahun 2010 tentang Pedoman Pelayanan Administrasi Terpadu Kecamatan (PATEN). Tujuan dari penelitian ini adalah untuk mendeskripsikan mengenai Implementasi Pelayanan Administrasi Terpadu Kecamatan di Kecamatan Gantar Kabupaten Indramayu Perspektif Peraturan Menteri Dalam Negeri Nomor 4 Tahun 2010 dan Fiqih Siyasah. Metode penelitian yang digunakan adalah metode penelitian kualitatif dengan pendekatan penelitian analisis deskriptif. Hasil penelitian Implementasi Pelayanan Admisitrasi Terpadu Kecamatan (PATEN) perspektif Peraturan Menteri Dalam Negeri Nomor 4 Tahun 2010 Kecamatan Gantar sudah memenuhi syarat penyelenggaraan PATEN baik mengenai syarat substantif, administratif dan teknis. Adapun faktor yang mempengaruhi keberhasilan pelaksanaan kebijakan yaitu, adanya komunikasi yang baik, disposisi dan struktur birokrasi yang dapat membuat implementasi PATEN berjalan dengan baik. Pelaksanaan kebijakan PATEN dalam Fiqih siyasah yang terjadi di kecamatan Gantar cukup baik, untuk merealisasikan kesempurnaan dalam melaksanakan pelayanan administrasi terdapat dua indikator yaitu cepat dalam pelayanan, dan profesional dalam penanganan. Namun indikator pelayanan administrasi pada Kantor Camat Gantar tersebut masih perlu ditingkatkan lebih baik lagi.Kata Kunci: Kebijakan; PATEN; Fiqih Siyasah